Measurement accuracy and reliability of self-reported versus measured weight and height among adults in Malaysia: Findings from a nationwide blood pressure screening programme - Chia, Yook Chin *; Ching, S. M.; Ooi, Pei Boon *; Beh, H. C.; Chew, Ming Tsuey *; Chung, Felicia Fei Lei *; Navin, Kumar; Lim, Hooi Min (PLOS, 2023)
Most studies reporting prevalence of obesity use actual weight and height measurements. Self-reported weight and height have been used in epidemiological studies as they have been shown to be reliable, convenient, and inexpensive alternatives to actual measurements. However, the accuracy of self-reported weight and height might vary in different regions because of the difference in health awareness and social influences. This study aims to determine the accuracy and reliability of self-reported weight and height compared to actual measured weight and height among adults in Malaysia. This was a cross-sectional study conducted at the community level during blood pressure screening campaigns. Participants self-reported their weight and height in a questionnaire survey. Their weight and height were validated using measurements by researchers on the same setting. Body mass index (BMI) was defined as underweight (<18.5kg/m2), normal (18.5–22.9 kg/m2), overweight (23–27.4 kg/m2) and obesity (≥27.5 kg/m2). Bland-Altman analysis, intraclass correlation coefficients and weighted Kappa statistics were used to assess the degree of agreement between self-reported and measured weight and height. A total of 2781 participants were recruited in this study. The difference between the mean self-reported and measured weight and height were 0.4 kg and 0.4 cm respectively. Weighted Kappa statistics analysis showed that there was a substantial agreement between the BMI classifications derived from self-reported and actual measurement (ҡ = 0.920, p<0.001). There was no marked difference in the sensitivity and specificity of self-reported BMI among Malaysian adults by gender. We observed substantial agreement between self-reported and measured body weight and height within a sample of Malaysian adults. While self-reported body weight showed weaker agreement with actual measurements particularly for obese and overweight individuals, BMI values derived from self-reported weight and height were accurate for 88.53% of the participants. We thus conclude that self-reported height and weight measures may be useful for tracking and estimating population trends amongst Malaysian adults.